# Thread: rearranging formula

1. ## rearranging formula

(z+h)+[(Q/b*(z+h))^2/(2*g)]=z

Could someone please solve for z.

We know all the variables apart from z.

Cheers

2. Well, this is the best I can make out from how you have the original problem written... learning to write this stuff in TEX on here can be helpful

$\displaystyle z+h+\frac{(\frac{Q}{b}(z+h))^2}{2g}=z$.

Is this the correct problem?

Btw, I don't think this belongs in this section... this really feels like more of a basic algebra question than abstract algebra or whatever.

But I'll help anyway since it's here.

What work have you been able to do yourself so far?

3. Originally Posted by Haris
(z+h)+[(Q/b*(z+h))^2/(2*g)]=z

Could someone please solve for z.

We know all the variables apart from z.

Cheers
If you introduce some new notation such as x = z + h and (Q/b)^2/2g = a it's much easier to see:

$\displaystyle x + ax^2 = x - h \Rightarrow ax^2 = -h$. If a < 0 then there is no real solution for x and hence z.